2010
DOI: 10.1182/blood.v116.21.3173.3173
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Risk Score for Cancer-Associated Thrombosis: Role of Screening In A Prospective Study

Abstract: 3173 Background: We evaluated the utility of screening for VTE using a previously developed clinical risk score (Khorana et al, Blood 2008) in a prospective cohort of cancer patients initiating outpatient chemotherapy but not receiving thromboprophylaxis. Methods: Cancer patients initiating a new chemotherapy regimen and deemed high-risk based on a predictive risk model (score ≥3) were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been shown to accurately predict the short-term risk of symptomatic VTE in patients undergoing chemotherapy-based treatments. The Khorana's clinical risk score is under evaluation in a prospective cohort of cancer patients initiating outpatient chemotherapy but not receiving thromboprophylaxis (65).…”
Section: Risk Stratificationmentioning
confidence: 99%
“…It has been shown to accurately predict the short-term risk of symptomatic VTE in patients undergoing chemotherapy-based treatments. The Khorana's clinical risk score is under evaluation in a prospective cohort of cancer patients initiating outpatient chemotherapy but not receiving thromboprophylaxis (65).…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Five risk factors were identified that were predictive of chemotherapy-related VTE ( Table 1 ). 16 This risk score was subsequently validated in multiple settings and evaluated in more than 12,000 patients 17 18 19 20 21 22 ( Table 2 ). 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37…”
Section: Introductionmentioning
confidence: 99%